1989
DOI: 10.1161/01.hyp.14.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of aortic smooth muscle cell membrane potential by extracellular calcium.

Abstract: Removal of extracellular calcium may result in depolarization of the resting cell membrane potential. This has been attributed to the stabilizing action of calcium on the ionic permeability of the cell membrane. It is unknown whether this phenomenon is exclusively mediated by extracellular calcium or through associated changes in intracellular calcium. To examine this, we exposed rat aortic smooth muscle cells in culture to different calcium concentrations and studied their effects on the resting membrane pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These observations suggest that vascular smooth muscle intracellular activator calcium concentration on exposure to a variety of agonists is independent of the variation in extracellular Ca 2+ level used in this study. This conclusion is consistent with the observation of Palant et al 24 on rat thoracic aorta; they failed to find a change in intracellular Ca 2+ using the dye fura 2-AM when extracellular Ca 2+ was reduced to 0.25 mM. Over the same range of calcium concentration, the membrane potential of the vascular smooth muscle from the common carotid artery does not vary significantly.…”
Section: +supporting
confidence: 92%
See 1 more Smart Citation
“…These observations suggest that vascular smooth muscle intracellular activator calcium concentration on exposure to a variety of agonists is independent of the variation in extracellular Ca 2+ level used in this study. This conclusion is consistent with the observation of Palant et al 24 on rat thoracic aorta; they failed to find a change in intracellular Ca 2+ using the dye fura 2-AM when extracellular Ca 2+ was reduced to 0.25 mM. Over the same range of calcium concentration, the membrane potential of the vascular smooth muscle from the common carotid artery does not vary significantly.…”
Section: +supporting
confidence: 92%
“…Webb and Bohr 26 proposed that the reduced response of vascular strips to norepinephrine was due to increased activity of the Na + ,K + -ATPase. Furspan et al 28 introduced the idea that "membranebound calcium" reinforces the stabilizing effect of an electrical field on the resting membrane, a concept subsequently supported in part by Palant et al 24 It has been suggested that membrane stabilization is associated with Ca 2+ binding by an integral membrane Ca 2+ binding protein that presumably stabilizes a variety of membrane-related mechanisms. 28 Lopez-Jaramillo et al 18 did not advance an explanation for the reduction they observed in NO production in high extracellular Ca* + .…”
Section: +mentioning
confidence: 99%
“…Intracellular calcium did not change when external calcium was increased from 0.25 to 1.8 mmol/L. 41 Intracellular sodium was found not to change when extracellular calcium was increased up to 1.8 mmol/L in cultured rat aortic smooth muscle cells. This was confirmed in cells cultured from the carotid artery of the same species.…”
Section: Changes In Extracellular Calciummentioning
confidence: 74%
“…In our study the threshold concentration of [Ca"], needed to repolarize the platelets was 20 pAM. A recent study has suggested that in vascular smooth muscle cells the active level of [Ca'-]<, is in the mALI range and may affect resting En, (22). Inoue et al (24) have recently described Ca'+-activated K+ channels in portal vein cells that are opened by [Ca'+], at a threshold of 0.2-7.5 pLM; a maximal response was reached at a concentration of greater than 600 p A V .…”
Section: Discussionmentioning
confidence: 99%